Alterações da expressão de genes de matriz extracelular e da familia TGFB nas lesões do manguito rotator - Figueiredo, Eduardo Antonio De [UNIFESP] (2019)
Introduction: Lack of synthesis of extracellular matrix compounds may contribute to degeneration of the tendons. Objective: we aimed to evaluate the expression of extracellular matrix and TGFB family members in ruptured and non-ruptured tendons of the rotator cuff, as well as the effect of clinical factors on gene expression in tendon samples, and the relationship between histological findings and altered gene expression. Methods: Injured and non-injured supraspinatus tendon samples and subscapular non-injured tendon samples were collected from 38 patients with rotator cuff tears. Noninjured supraspinatus tendons were obtained from eight controls. Specimens were used for histological evaluation, quantification of collagen fibers, and mRNA and protein expression analyses. Results: Increased COL1A1, COL1A2, COL3A1, COL5A1, FN1, TNC, and TGFBR1 mRNA expression was observed in the tear samples (p < 0.05). Duration of symptoms was correlated with the levels of collagen type I/III fibers (p = 0.032; p = 0.0447) and FN1 immunostaining (p = 0.031; p = 0.417). Smoking was associated with increased frequency of microcysts, myxoid degeneration, and COL5A1, FN1, TNC, and TGFB1 mRNA expression (p < 0.05). FN1 immunostaining was correlated with the number of years of smoking (p=0.048; p=0.384). Lower levels of collagen type I/III fibers were detected in samples with fissures (p=0.046). High frequency of microcysts was associated with increased COL5A1, FN1, and TNC expression (p < 0.05, for all comparisons). Neovascularization was associated with reduced FN1 (p=0.035) and TGFBR1 expression (p=0.034). Conclusion: Our findings show differential expression of matrix extracellular genes and TGFB family members in the degeneration process involved in rotator cuff tears. These molecular alterations are influenced by clinical factors.